Parental Reports on the Efficacy of Applied Behavior Analysis based intervention for children with Autism Spectrum Disorder in UAE. - BHUPTANI, NIPA AJAY (2017)
This study was conducted to investigate the views of parents of children with Autism Spectrum Disorder regarding the efficacy of intervention based on Applied Behavior Analysis, for their child, in United Arab Emirates. Data was collected via electronic survey questionnaire, parent interviews and literature research. Although the findings of this study are positive, it highlighted the gaps in the field and the need for further research in order to create more availability of intervention services and establish regulation in the area of services for Autism and specifically for Applied Behavior Analysis in UAE.